2022
DOI: 10.3390/ijms23041974
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and MDMA (Ecstasy) Exacerbate ER Stress Triggered by Hyperthermia

Abstract: Drugs of abuse can cause local and systemic hyperthermia, a known trigger of endoplasmic reticulum (ER) stress and the unfolded protein response (UPR). Another trigger of ER stress and UPR is ER calcium depletion, which causes ER exodosis, the secretion of ER-resident proteins. In rodent models, club drugs such as 3,4-methylenedioxymethamphetamine (MDMA, ‘ecstasy’) can create hyperthermic conditions in the brain and cause toxicity that is affected by the environmental temperature and the presence of other drug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…ERS tails of proteins that move from ER to Golgi interact with KDEL receptors located in the Golgi and cause retrograde transport of the ERS-containing proteins from the Golgi back to the ER. We have previously shown that augmenting KDELR expression can attenuate exodosis caused by thapsigargin, hypoxia and hyperthermia 13,33 . We first investigated the ability of KDELR to influence Tg-induced GLuc-SERCaMP secretion in rat primary neurons transduced with AAV vectors expressing GLuc-SERCaMP and eYFP (control), KDELR1, or KDELR2.…”
Section: Kdelr1 and Kdelr2 Diminish Tg-induced Gluc-sercamp Secretionmentioning
confidence: 99%
“…ERS tails of proteins that move from ER to Golgi interact with KDEL receptors located in the Golgi and cause retrograde transport of the ERS-containing proteins from the Golgi back to the ER. We have previously shown that augmenting KDELR expression can attenuate exodosis caused by thapsigargin, hypoxia and hyperthermia 13,33 . We first investigated the ability of KDELR to influence Tg-induced GLuc-SERCaMP secretion in rat primary neurons transduced with AAV vectors expressing GLuc-SERCaMP and eYFP (control), KDELR1, or KDELR2.…”
Section: Kdelr1 and Kdelr2 Diminish Tg-induced Gluc-sercamp Secretionmentioning
confidence: 99%